2022
DOI: 10.1128/spectrum.02716-21
|View full text |Cite
|
Sign up to set email alerts
|

Toward Optimization of a Rabbit Model of Staphylococcus aureus (USA300) Skin and Soft Tissue Infection

Abstract: Animal models of S. aureus infection are important for evaluating bacterial pathogenesis and host immune responses. These animal infection models are often used as an initial step in the testing of vaccine antigens and new therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Owing to these characteristics, they are commonly used experimentally for pyrogenic, immunological, and pharmacological studies. Malachowa ( Malachowa et al, 2022 ), among others, demonstrated the successful optimization of Staphylococcus aureus skin infection in rabbits, which provides a reference for the establishment of other skin infection models. The present study aimed to characterize the laboratory-isolated P. aeruginosa phage PaVOA and subsequently evaluate its efficacy in resolving P. aeruginosa -mediated wound infections in New Zealand rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these characteristics, they are commonly used experimentally for pyrogenic, immunological, and pharmacological studies. Malachowa ( Malachowa et al, 2022 ), among others, demonstrated the successful optimization of Staphylococcus aureus skin infection in rabbits, which provides a reference for the establishment of other skin infection models. The present study aimed to characterize the laboratory-isolated P. aeruginosa phage PaVOA and subsequently evaluate its efficacy in resolving P. aeruginosa -mediated wound infections in New Zealand rabbits.…”
Section: Introductionmentioning
confidence: 99%